Integrated automation system of coal mine based on data fusion technology - GU Shanmao; HE Fengyou; LIU Yunlong (Gong-kuang zidonghua, 2015)
Main problems of existing integrated automation system of coal min were analyzed, namely information island, low running reliability of bottom sensor, low system data fusion degreed, etc. Establishment keys of integrated automation system of coal mine were pointed out, which were running reliability detection of each production system and deep data mining and fusion. Key technologies of the system establishment were proposed, which were intelligent sensor and data fusion function, and solutions of data fusion were given from aspects of software fusion, system fusion and function fusion. An integrated automation system of coal mine based on C# programming has been applied in a coal mine successfully with a good effect.